The Role of Teachers in the Dissemination of Learning Processes through Scientific Journal Publications - Hesti Herliantari (Science Center Group, 2024)
The role of teachers in the learning process is not limited to classroom activities but also includes scientific publications as a means of disseminating knowledge to the broader community. Purpose: This article aims to examine the role of scientific publications by teachers in enhancing learning quality and professional development. Method: A perspective method was applied with a descriptive qualitative approach, reviewing literature on the role of teachers in scientific publications and its impact on educational quality improvement. Results: The study shows that scientific publications by teachers are significant in enhancing academic credibility, innovating teaching methods, and developing teacher competencies. Conclusion: Scientific publications serve as indicators of professionalism and as a medium for disseminating best teaching practices. Suggestion: Support from educational institutions in the form of training and mentorship is essential for actively engaging teachers in scientific publications.